Students’ perceptions of personality traits, presentation skills, and audience factors in their online presentations - Roslim, Norwati; Nimehchisalem, Vahid; Abdullah, Muhammad Hakimi Tew; Mohd Razali, Nornadiah (University Press, Universitas Syiah Kuala, 2023)
This study aims to investigate undergraduates’ perspectives toward personality traits, presentation skills, and audience factors based on their experiences in online oral presentations as assessment tasks during English language classes. It also examines the factors affecting online oral presentations and suggestions to overcome them. To achieve this purpose, an online questionnaire with 5 sections and 28 items was distributed to 90 university undergraduate students. The data were analyzed descriptively using SPSS (version 26).  The results revealed that the undergraduates’ perceptions of online oral presentations depended on three essential factors. Personality traits included fears of failure in the oral presentation assessment resulting in students’ anxiety even when they were well prepared. Oral presentation skills included their concerns on grammar, vocabulary, pronunciation, and reading from notes during the oral presentation. The audience included feeling frightened to present in front of an audience and worried if their peers were better than them. To conclude, the important factors that students realized were the audience, personality traits, and presentation skills. Hence, suggestions that students had provided included having enough preparation and practice as well as receiving good support from lecturers. This study highlights the vital role of lecturers in preparing learners for online oral presentations and underscores the need for guiding effective preparation strategies such as practice sessions.